Sources of Government Approval During the COVID-19 Pandemic: Threat or Electoral Predispositions? - Adrián Pignataro (SAGE Publishing, 2021)
Rally-round-the-flag events are short-term boosts of government approval during crises, and the COVID-19 pandemic produced such an effect in many countries. But why did some people join the rally while others didn’t? Using public opinion data from Costa Rica, this paper tests two hypotheses: first, that threat increases government approval at the outbreak of the pandemic; second, that electoral predispositions shape approval. Results indicate that COVID-19 contagions, as a measure of the threat, are not associated with approval, while past voting patterns are. Positive assessments of the economy and the relief measures also predict higher support for the government. In brief, Costa Rica's rally-round-the-flag event did not overcome the partisan divisions or the ordinary drivers of approval.